Variation of Meiotic Recombination Rates and MLH1 Foci Distribution in Spermatocytes of Cattle, Sheep and Goats - Fröhlich, Jan; Vozdova, Miluse; Kubickova, Svatava; Cernohorska, Halina; Sebestova, Hana; Rubes, Jiri (Cytogenetic and genome research, 2015)
Despite similar genome sizes, a great variability in recombination rates is observed in mammals. We used antibodies against SYCP3, MLH1 and centromeres to compare crossover frequency, position along chromosome arms and the effect of crossover interference in spermatocytes of 4 species from the family Bovidae (Bos taurus, 2n = 60, tribe Bovini; Ovis aries, 2n = 54, Capra hircus, 2n = 60 and Ammotragus lervia, 2n = 58, tribe Caprini). Despite significant individual variability, our results also show significant differences in both recombination rates and the total length of autosomal synaptonemal complexes (SC) between cattle (47.53 MLH1 foci/cell, 244.59 µm) and members of the tribe Caprini (61.83 MLH1 foci, 296.19 µm) which can be explained by the length of time that has passed since their evolutionary divergence. Sheep displayed the highest number of MLH1 foci per cell and recombination density, although they have a lower diploid chromosome number caused by centric fusions corresponding to cattle chromosomes 1;3, 2;8 and 5;11. However, the proportion of MLH1 foci observed on the fused chromosomes in sheep (26.14%) was significantly lower than on the orthologous acrocentrics in cattle (27.6%) and goats (28.2%), and their distribution along the SC arms differed significantly. The reduced recombination rate in metacentrics is probably caused by interference acting across the centromere.
Keywords: Cattle; kozy; Male; hybridizace in situ fluorescenční; Goats; skot; jaderné proteiny; Meiosis; mužské pohlaví; ovce; Sheep; meióza; Animals; spermatocyty; Spermatocytes; zvířata; Recombination, Genetic; rekombinace genetická; In Situ Hybridization, Fluorescence; Nuclear Proteins